Inkjet printing of UV-curable adhesive and dielectric inks for microfluidic devices. Issue 1 (2nd December 2015) - Hamad, E. M.; Bilatto, S. E. R.; Adly, N. Y.; Correa, D. S.; Wolfrum, B.; Schöning, M. J.; Offenhäusser, A.; Yakushenko, A.
Abstract : Bonding 3D-printed microfluidic systems to polymeric substrates using inkjet-printed dielectric adhesives. Abstract : Bonding of polymer-based microfluidics to polymer substrates still poses a challenge for Lab-On-a-Chip applications. Especially, when sensing elements are incorporated, patterned deposition of adhesives with curing at ambient conditions is required. Here, we demonstrate a fabrication method for fully printed microfluidic systems with sensing elements using inkjet and stereolithographic 3D-printing.